TEACHING ENGLISH GRAMMAR WITH DICTOGLOSS - Hermansyah Hermansyah; Herlina Santoso (Politeknik Negeri Sriwijaya, 2018)
This paper investigated the used of dictogloss in teaching English grammar. Dictogloss offers a context-rich method of assessing how much students know about the topic of the text. Two tests were given to the students, a pre-test and a post-test. It was found that the students’ score in the posttest (82) was significantly higher than that in the pre-test (59). The writers examined the student’ note taking on the linguistic components and grammatical structures by focusing on certain grammar items, accuracy and meaning. Note taking or composition was scored by using a marking system. By using dictogloss the teacher reinforce students’ mastery in learning English grammar.